Effect of sintering temperature and boron carbide content on the wear behavior of hot pressed diamond cutting segments - Islak S.; Çelik H. (National Library of Serbia, 2015)
The aim of this study was to investigate the effect of sintering temperature and boron carbide content on wear behavior of diamond cutting segments. For this purpose, the segments contained 2, 5 and 10 wt.% B4C were prepared by hot pressing process carried out under a pressure of 35 MPa, at 600, 650 and 700 ?C for 3 minutes. The transverse rupture strength (TRS) of the segments was assessed using a three-point bending test. Ankara andesite stone was cut to examine the wear behavior of segments with boron carbide. Microstructure, surfaces of wear and fracture of segments were determined by scanning electron microscopy (SEM-EDS), and X-ray diffraction (XRD) analysis. As a result, the wear rate decreased significantly in the 0-5 wt.% B4C contents, while it increased in the 5-10 wt.% B4C contents. With increase in sintering temperature, the wear rate decreased due to the hard matrix.
Keywords: wear; Diamond cutting segments; Chemical technology; TRS; TP1-1185; B4C; sintering temperature